KI 2008: Advances in Artificial Intelligence 31st Annual German Conference on AI, KI 2008, Kaiserslautern, Germany, September 23-26, 2008. Proceedings - Dengel, Andreas R.; Berns, Karsten; Breuel, Thomas M.; Bomarius, Frank; Roth-Berghofer, Thomas R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book constitutes the thoroughly refereed proceedings of the 31th Annual German Conference on Artificial Intelligence, KI 2008, held in Kaiserslautern, Germany, September 2008. The 15 revised full papers presented together with 2 invited contributions and 30 posters were carefully reviewed and selected from 77 submissions. The papers cover important areas such as pattern recognition, multi-agent systems, machine learning, natural language processing, constraint reasoning, knowledge representation and management, planning, and temporal reasoning.
Invited Talks -- Folk Reducibility and AI-Complete Problems -- Meme Media and Knowledge Federation -- Papers -- Navidgator - Similarity Based Browsing for Image and Video Databases -- Automating Interactive Protocol Verification -- Iterative Search for Similar Documents on Mobile Devices -- Limits and Possibilities of BDDs in State Space Search -- Interactive Dynamic Information Extraction -- Fusing DL Reasoning with HTN Planning -- Multi-value Classification of Very Short Texts -- Analysis and Evaluation of Inductive Programming Systems in a Higher-Order Framework -- High-Level Expectations for Low-Level Image Processing -- Automatic Bidding for the Game of Skat -- Automobile Driving Behavior Recognition Using Boosting Sequential Labeling Method for Adaptive Driver Assistance Systems -- Identifying and Analysing Germany$1 (Bs Top Blogs -- Planar Features for Visual SLAM -- Extracting and Querying Relations in Scientific Papers -- Efficient Hierarchical Reasoning about Functions over Numerical Domains -- A Drum Machine That Learns to Groove -- Posters -- Believing Finite-State Cascades in Knowledge-Based Information Extraction -- A Methodological Approach for the Effective Modeling of Bayesian Networks -- Plan Repair in Hybrid Planning -- Visual Terrain Traversability Estimation Using a Combined Slope/Elevation Model -- Symbolic Classification of General Two-Player Games -- Partial Symbolic Pattern Databases for Optimal Sequential Planning -- Optimal Scheduling with Resources for Application Execution in 3G Networks -- ESO: Evolutionary Self-organization in Smart-Appliances Ensembles -- On-Line Detection of Rule Violations in Table Soccer -- Extracting and Verifying Hyponymy Relations Based on Multiple Patterns and Features -- News Annotations for Navigation by Semantic Similarity -- EANT+KALMAN: An Efficient Reinforcement Learning Method for Continuous State Partially Observable Domains -- Where Temporal Description Logics Fail: Representing Temporally-Changing Relationships -- Interpreting Motion Expressions in Route Instructions Using Two Projection-Based Spatial Models -- Repairing Decision-Theoretic Policies Using Goal-Oriented Planning -- A Recognition Interface for Bridging the Semantic Desktop and the Physical World -- Learning by Observing: Case-Based Decision Making in Complex Strategy Games -- Toward Alignment with a Virtual Human - Achieving Joint Attention -- Concerning Olga, the Beautiful Little Street Dancer: Adjectives as Higher-Order Polymorphic Functions -- FACT-Graph: Trend Visualization by Frequency and Co-occurrence -- Enhancing Animated Agents in an Instrumented Poker Game -- Shallow Models for Non-iterative Modal Logics -- Homography Based State Estimation for Aerial Robots -- A Symbolic Pattern Classifier for Interval Data Based on Binary Probit Analysis -- Object Configuration Reconstruction from Incomplete Binary Object Relation Descriptions -- Visual-Based Emotion Detection for Natural Man-Machine Interaction -- Simplest Scenario for Mutual Nested Modeling in Human-Machine-Interaction -- Bayesian Network for Future Home Energy Consumption -- Learning Dance Movements by Imitation: A Multiple Model Approach -- Demos -- Ontology-Based Information Extraction and Reasoning for Business Intelligence Applications -- A Scalable Architecture for Cross-Modal Semantic Annotation and Retrieval -- Prototype Prolog API for Mindstorms NXT -- VARDA Rule Design and Visualization Tool-Chain -- COSAIR: A Platform for AI Education and Research in Computer Strategy Games -- Research Center Ambient Intelligence: Assisted Bicycle Team Training.s
Keywords: Computer science; Mathematical logic; Data mining; Information storage and retrieval; Multimedia information systems; Artificial intelligence; Computational linguistics; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Mathematical Logic and Formal Languages; Language Translation and Linguistics; Multimedia Information Systems; Information Storage and Retrieval; Electronic books